Heterotrimeric G Protein-coupled Receptor Signaling in Yeast Mating Pheromone Response - Alvaro, Christopher G. (J Biol Chem, 2016)
The DNAs encoding the receptors that respond to the peptide mating pheromones of the budding yeast Saccharomyces cerevisiae were isolated in 1985, and were the very first genes for agonist-binding heterotrimeric G protein-coupled receptors (GPCRs) to be cloned in any organism. Now, over 30 years later, this yeast and its receptors continue to provide a pathfinding experimental paradigm for investigating GPCR-initiated signaling and its regulation, as described in this retrospective overview.